Electron transport across electrically switchable magnetic molecules - SANVITO, STEFANO (My University, 2009)
We investigate the electron-transport properties of a model magnetic molecule formed by two magnetic centers whose exchange coupling can be altered with a longitudinal electric field. In general, we find a negative differential conductance at low temperatures originating from the different scattering amplitudes of the singlet and triplet states. More interestingly, when the molecule is strongly coupled to the leads and the potential drop at the magnetic centers is only weakly dependent on the magnetic configuration, we find that there is a critical voltage V C at which the current becomes independent of the temperature. This corresponds to a peak in the low-temperature current noise. In such limit, we demonstrate that the quadratic current fluctuations are pro- portional to the product between the conductance fluctuations and the temperature
PUBLISHED
Keywords: Physics; Nanoscience & Materials